Terminal year-end report: Retro Radar Corporation - Baclig, Sheiji (Animo Repository, 2021)
Retro Radar is a corporation that stemmed out of our passion for sustainability and fashion. The company focuses on selling vintage, reworked and one of a kind pieces. It is probably not known to all that the fashion industry comes in second place in the hierarchy of the world's largest pollutants and environmental damage continues to increase as the industry grows. It becomes quite difficult not to succumb into the hole of fast fashion especially when trends are continuously arising and changing. It is quite literal that coming from the term 'fast fashion', it means the easiest, most accessible and affordable way on how to keep up with those trends because of the nature of how these clothing pieces were produced. Clothing pieces manufactured by the fast fashion industry practice unethical treatment that are harmful not only to the environment, but to their employees as well. The nature of production in this industry is what makes it possible for thousands of clothing pieces to be produced from the initial design to final product in as fast as just four days. This process does not give importance to quality reassurance because of the negligence the industry has in caring for their employees and the environment. These companies settle for poor quality production and unethical treatment to their employees because either way, a profit will be returned due to the very low cost put into production. Retro radar aims to take a step in the right direction to address these concerns in whatever way we can. We want to align sustainability with fashion by offering one of a kind pieces that customers can score and feel like they have a special piece that no one else owns. We want to prove that you do not need to sacrifice fashion and keeping up with trends in order to practice sustainability. Retro radar aims to give our customers an option to shop sustainably without sacrificing their love for fashion and diversity. As a team, we took this as an opportunity to penetrate the fashion industry by promoting our love for unique, one of a kind pieces. We were able to do this by curating and building different clothing collection through sourcing second hand clothing pieces and giving it back its life and giving it a new home. By doing this, we are able to continue the life cycle of a clothing pieces and promote sustainability by making those pieces accessible for others to shop and to enjoy as well.